Internalizing Moral Education Values in Sufism: A Comparative Study of Al-Ghazali’s and Ibn Taymiyyah’s Thought - Lalan Sahlani; Arie Noviana; Dodi Misbah Jalaludin; M. Tajudin Zuhri (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The rapid transformation of modern society has significantly affected the structure and function of Muslim families, particularly in relation to moral formation and religious education within the household. The dominance of materialism, technological disruption, and the increasing delegation of parenting responsibilities to external institutions have contributed to weakening family-based Islamic values. This study aims to analyze and reconstruct K.H. Miftah Faridl’s concept of family-based Islamic education as a framework for strengthening moral resilience in the age of disruption. This research employed a qualitative descriptive design using a figure study approach. Data were collected through in-depth interviews, document analysis, and literature review focusing on Miftah Faridl’s major works related to Islamic family education. The data were analyzed using qualitative content analysis through coding, categorization, thematic interpretation, and conceptual synthesis. The findings reveal that Faridl conceptualizes family education as a comprehensive theological and sociological process rooted in the Qur’an and Sunnah. Parents are positioned as the primary educational agents responsible for cultivating faith, morality, emotional attachment, and Islamic identity within the household. The study also found that Faridl emphasizes holistic curriculum development, role modeling (uswatun hasanah), affective communication, spiritual intervention through prayer, and the construction of a supportive sociocultural ecosystem involving families, schools, mosques, and society. The study concludes that family-based Islamic education functions not only as a private educational activity but also as a strategic mechanism for preserving moral resilience and sustaining Islamic civilization amidst the challenges of modern social disruption.